Reframing South African TV news as peace journalism - Jake Lynch (Communicare)
This article presents an indicative sample from the results of an experiment that gathered audience responses to television news that was coded as “war journalism” and “peace journalism” respectively, in South Africa, during April 2012. From the peace journalism model, evaluative criteria were derived under a set of five headings for content analysis of two television news programmes and four newspapers. Distinctions under the headings were particularised for individual stories by critical discourse analysis to disclose potential sources of influence transmitted into audience frames. The test material was then coded to fall within the upper and lower peace journalism quartiles of the ‘idiom and range’ of journalism, as currently practised, demonstrated by the content analysis. Transcripts of discussions by focus groups who saw the material, as well as written notes made whilst viewing by a larger sample of participants, were themed according to Entman’s model of framing (1993), where causal interpretation is linked to treatment recommendation. From these interim findings, peace journalism proved to be ideational in the sense that peace journalism viewers were more likely to perceive structural and/or systemic explanations for problems, and more likely to see opportunities for therapeutic and/or cooperative remedies to be applied through exertions of political agency from different levels.